Prognostic value of dynamic albumin-to-alkaline phosphatase ratio in limited stage small-cell lung cancer. (15th January 2019) - Li, Xiaogang; Li, Butuo; Zeng, Haiyan; Wang, Shijiang; Sun, Xindong; Yu, Yishan; Wang, Linlin; Yu, Jinming
Aim: To dynamically investigate the prognostic value of albumin-to-alkaline phosphatase ratio (AAPR) in limited stage small-cell lung cancer.Materials & methods: The AAPR within 1 week before and after chemoradiation therapy (pre- and post-AAPR) was collected and analyzed.Results: Patients with low pre- or post-AAPR had shorter overall survival and progression-free survival than the high groups (p-values all <0.05). Post-AAPR was an independent prognostic factor for progression-free survival (p = 0.007) and overall survival (p = 0.003). The integration of pre- or post-AAPR improved the prognostic ability of Tumor, Node, Metastasis stage alone (0.55–0.64 and 0.68, respectively).Conclusion: Post-AAPR is a reliable prognostic factor for limited stage small-cell lung cancer patients. The complementary value of AAPR to Tumor, Node, Metastasis stage is worth further validation in the future.